2014
DOI: 10.2478/johr-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Some Plant Growth Regulators And Their Combination With Methyl Jasmonate On Anthocyanin Formation In Roots Of Kalanchoe Blossfeldiana

Abstract: In this study, we investigated the effect of plant growth regulators (PGRs) -auxins, gibberellin, cytokinin, abscisic acid, brassinosteroid, ethylene and their interaction with methyl jasmonate (JA-Me) applied to roots of the whole plants Kalanchoe blossfeldiana on the accumulation of anthocyanins in roots. The highest stimulation of anthocyanins synthesis was stated with application of JA-Me alone. In response to treatments with the other tested PGRs, the content of anthocyanins in roots of a whole plant was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Positive impact on the biosynthesis of anthocyanin has been established for plant hormones, such as gibberellins (Goraj et al, 2014). Gibberellins (GA 3 ) have been found to enhance a number of desirable factors including anthocyanin contents; Ohlsson and Berglund (2001) reported that application of GA 3 increased anthocyanin content in Catharanthus roseus.…”
Section: Introductionmentioning
confidence: 99%
“…Positive impact on the biosynthesis of anthocyanin has been established for plant hormones, such as gibberellins (Goraj et al, 2014). Gibberellins (GA 3 ) have been found to enhance a number of desirable factors including anthocyanin contents; Ohlsson and Berglund (2001) reported that application of GA 3 increased anthocyanin content in Catharanthus roseus.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time increased the quantum ef ciency of energy trapping in PSII and ef ciency index was accompanied by decrease in energy dissipation suggesting more effective energy usage. Methyl jasmonate (JA-Me) is an elicitor that causes the formation of anthocyanins in roots of Kalanchoe blossfeldiana (Góraj et al, 2014;Góraj-Koniarska et al, 2015). The anthocyanins are accumulated in roots of intact plants, but not in excised roots.…”
Section: Effect Of Multiwalled Carbon Nanotubes In Common Wheatmentioning
confidence: 99%
“…The color of the taproots varies from white to red, to purple-pink, to green, to bicolor, due to its accumulation of large amounts of anthocyanins (Chen et al, 2016). Studies on anthocyanin and the underlying molecular mechanism in radish dwell on single-tissue analysis and mostly at maturity stage (Park et al, 2011; Bae et al, 2012; Chen et al, 2016). A growing body of research provides evidence that as growth advances, anthocyanin accumulation is not localized in the plant but rather, discriminatively accumulates in specific clusters of cells located in different plant tissues (Zuluaga et al, 2008; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%